Iodination of human thyroglobulin (Tg) alters its immunoreactivity. II. Fine specificity of a monoclonal antibody that recognizes iodinated Tg - Saboori, A M (Blackwell Publishing Ltd, 1998)
In a previous investigation, we found that murine MoAb 42C3, raised against human Tg, recognized Tg differently depending upon its level of iodination of Tg. A possible explanation for this finding is that iodine is directly involved with the specific epitope recognized by MoAb 42C3. In the present study, we report that the binding of MoAb 42C3 to iodinated Tg is inhibited by T4, T3, reverse T3 (rT3), triiodothyroacetic acid (triac), diiodothyronine (T2), diiodotyrosine (DIT), but not by thyronine (T0) or tyrosine. The order of inhibition of these iodinated compounds is T4 > T3 > rT3 > triac > T2 > DIT. The MoAb 42C3 does not have the same specificity as the T3, T4-receptor since the order of binding of these iodinated compounds on the receptor differed from the order of their inhibition of this MoAb. Monoclonal antibody 42C3 also recognized non-iodinated Tg that was subsequently iodinated in vitro. It failed to recognize another protein, bovine serum albumin, that was iodinated in vitro by the same method. These results suggest that iodinated tyrosines and thyronines determine the binding specificity of MoAb 42C3. The inhibitory effects of these compounds on MoAb 42C3 depend on their iodine content as well as location of iodine in the aromatic ring.